A Systematic Review of Prerequisites for Constructability Implementation in Infrastructure Projects - Rozita Samimpey; Ehsan Saghatforoush (Civil Engineering Journal, 2020)
Success in infrastructure projects requires success in all phases of the project, including design, construction, and operation. One of the necessary actions for developing countries to construct their economic infrastructures, is implementing infrastructure plans. This industry should focus more on the construction process and utilizing creative tools and new concepts for construction development. The reason of it is because of delivering the project with certain quality, in time and with the given budget. Contractors should have new strategies for construction to optimize project completion, and constructability. Accordingly, constructability improvements have become the concern of construction industry practitioners. Considering constructability issues in the early stages of the project enhances identifying design limitations that prevent capabilities of contractors to take part in planning and improving project performance. The purpose of this study is identifying the prerequisites of constructability to resolve the current problems of projects, including inappropriate plans without implementability, poor decision making in design, and lack of sufficient implementation experience in the design engineering team. This study provides a list of prerequisites for constructability implementation in infrastructure projects. Accordingly, it identifies the prerequisites, using Systematic Literature Review (SLR) technique. The NVivo software is used to facilitate the qualitative analyses.